2016
DOI: 10.1016/j.exer.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of particles, small molecules and polymeric formulation excipients in the suprachoroidal space after microneedle injection

Abstract: The purpose of this work was to determine the effect of injection volume, formulation composition, and time on circumferential spread of particles, small molecules and polymeric formulation excipients in the suprachoroidal space (SCS) after microneedle injection into New Zealand White rabbit eyes ex vivo and in vivo. Microneedle injections of 25–150 μL Hank’s Balanced Salt Solution (HBSS) containing 0.2 μm red-fluorescent particles and a model small molecule (fluorescein) were performed in rabbit eyes ex vivo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Rheological properties of the polymer are important in this regard: high MW and moderately non-Newtonian polymeric solutions (e.g., HA) enhance particle spreading, whereas strongly non-Newtonian polymer solutions (e.g., methylcellulose, CMC) are immobilized at the injection site. For example, an injected solution of Discovisc (1.6 MDa HA) is eliminated in one week, while 700 kDa CMC is retained at injection site for 3 weeks [186].…”
Section: Suprachoroidal Deliverymentioning
confidence: 99%
“…Rheological properties of the polymer are important in this regard: high MW and moderately non-Newtonian polymeric solutions (e.g., HA) enhance particle spreading, whereas strongly non-Newtonian polymer solutions (e.g., methylcellulose, CMC) are immobilized at the injection site. For example, an injected solution of Discovisc (1.6 MDa HA) is eliminated in one week, while 700 kDa CMC is retained at injection site for 3 weeks [186].…”
Section: Suprachoroidal Deliverymentioning
confidence: 99%
“…The team also employed a conventional 27-gauge needle to deliver AAV8 suprachoroidally in three nonhuman primates, 56 but this free-hand technique is less precise and cannot exclude the possibility of inadvertent subretinal delivery. In contrast, our study employed rhesus macaques with ocular dimensions and vasculature similar to humans, and transscleral microneedles, which reliably access the suprachoroidal space with well-characterized biodistribution, 57,58 and are already employed in human patients in phase I/II clinical trials. 42,59 We also employed in vivo SLO imaging, demonstrating the striking, unique expression pattern of suprachoroidal AAV8, consistent with the anatomic characteristics of the choroidal-scleral junction, which differs from subretinal or intravitreal AAV8 delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that increasing injection volume resulted in increasing coverage area[65, 66, 68, 71, 75, 81]. However, it was difficult to cover 100%, likely due to anatomical barriers[80].…”
Section: Pharmacokinetics Within the Suprachoroidal Spacementioning
confidence: 99%
“…Polymeric formulations (such as hyaluronic acid) are hypothesized to spread well after injections since they exert an osmotic pressure that seeks to imbibe fluid, resulting in expansion of the formulation, and may also coat particles and/or tissue to prevent non-specific binding. By tracking the distribution of particles and fluid formulations simultaneously, the injected fluid traveled further into the SCS than the injected particles when using low-viscosity formulations, suggesting some degree of particle entrapment with the SCS; with high-viscosity formulations, the discrepancy between the travel distance of the particle and polymeric formulation was decreased [81]. These findings suggest that these viscous formulations increased transit time in the SCS, and reduced particle-tissue interactions[81].…”
Section: Pharmacokinetics Within the Suprachoroidal Spacementioning
confidence: 99%
See 1 more Smart Citation